HerMES: THE REST-FRAME UV EMISSION AND A LENSING MODEL FOR THE z=6.34 LUMINOUS DUSTY STARBURST GALAXY HFLS3 - Cooray, A; Calanog, J; Wardlow, J; Bock, J; Bridge, C; Burgarella, D; Bussmann, R; Casey, C; Clements, D; Conley, A; Farrah, D; Fu, H; et al. (Institute of Physics Publishing, 2014)
We discuss the rest-frame ultraviolet emission from the starbursting galaxy HFLS3 at a redshift of 6.34. The galaxy was discovered in Herschel/SPIRE data due to its red color in the submillimeter wavelengths from 250 to 500 μm. Keck/NIRC2 K s -band adaptive optics imaging data showed two potential near-IR counterparts near HFLS3. Previously, the northern galaxy was taken to be in the foreground at z = 2.1, while the southern galaxy was assumed to be HFLS3's near-IR counterpart. The recently acquired Hubble/WFC3 and Advanced Camera for Surveys (ACS) imaging data show conclusively that both optically bright galaxies are in the foreground at z < 6. A new lensing model based on the Hubble imaging data and the millimeter-wave continuum emission yields a magnification factor of 2.2 ± 0.3, with a 95% confidence upper limit on the magnification of 3.5. When corrected for lensing, the instantaneous star formation rate is 1320 M yr-1, with the 95% confidence lower limit around 830 M yr-1. The dust and stellar masses of HFLS3 from the same spectral energy distribution (SED) models are at the level of 3 × 10 8 M and 5 × 1010 M , respectively, with large systematic uncertainties on assumptions related to the SED model. With Hubble/WFC3 images, we also find diffuse near-IR emission about 0.5 arcsec (3 kpc) to the southwest of HFLS3 that remains undetected in the ACS imaging data. The emission has a photometric redshift consistent with either z 6 or a dusty galaxy template at z 2. © 2014. The American Astronomical Society. All rights reserved..